"I felt like a conspiracy theorist". - Bernstein, Jon (New Statesman, 2011)
The article focuses on Tom Watson, member of British Parliament (MP) and former Cabinet Office minister under former Prime Minister Gordon Brown. Information is provided on his role in the questioning of media mogul Rupert Murdoch and his son James Murdoch on the telephone hacking scandal at a Parliamentary hearing on July 19, 2011.